2020
DOI: 10.9734/arjom/2020/v16i1030228
|View full text |Cite
|
Sign up to set email alerts
|

Concept of Outlier Study: The Management of Outlier Handling with Significance in Inclusive Education Setting

Abstract: Collection of data and to check its suitability is the first step in any statistical data analysis. In such analyses, the presence of outliers appears as an unavoidable important problem. Outliers are unexpected random values in dataset, and they can alter the statistical conclusion and also affect their assumptions. Thus, in order to manage the data properly, outliers must be defined and treated. So all statisticians have to confront the analysis and forced to take a decision. There is only being one of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Outliers are observations that are different from the majority of other cases in a sample. 23 This study revealed item number 1C13: "doctor presents at the Posbindu" and 2C31: "providing medicine" were outliers.…”
Section: Resultsmentioning
confidence: 81%
“…Outliers are observations that are different from the majority of other cases in a sample. 23 This study revealed item number 1C13: "doctor presents at the Posbindu" and 2C31: "providing medicine" were outliers.…”
Section: Resultsmentioning
confidence: 81%
“…According to Walker et al (2018), the boxplot is still relevant to use in detecting any data beyond the normal or skewed distribution. At this stage, extreme data is taken out as an outlier (Mahapatra et al 2020). The data found beyond the boxplot have been taken out in order to avoid extreme data that may cause inefficient results (Mahapatra et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…At this stage, extreme data is taken out as an outlier (Mahapatra et al 2020). The data found beyond the boxplot have been taken out in order to avoid extreme data that may cause inefficient results (Mahapatra et al 2020). In summary, data gathered are data from 60 firms for ESG disclosure, 62 firms for environmental disclosure (ENV), 58 firms for social disclosure (SOC) and 57 firms for governance disclosure (GOV) with seven years of observations.…”
Section: Methodsmentioning
confidence: 99%
“…Pengecekan outlier dillakukan dengan cara memvisualisasikan melalui boxplot dapat memperlihatkan bahwa nilai-nilai ekstrim dalam kolom-kolom yang bersifat kontinu [10]. Namun, perlu dicatat bahwa dalam dataset ini, beberapa kolom memiliki tipe data kategorikal yang tidak cocok untuk visualisasi dengan metode tersebut.…”
Section: Metodologiunclassified